Effectiveness of Implementing Problem-Based Learning to Improve Critical Thinking Skills - Sopiansah, Veri Aryanto; Ramafrizal, Yudho (Jurnal Pendidikan Ekonomi, 2025)
The realization of a quality society is not sufficiently responsible for the world of education, especially in preparing participants to become increasingly hot topics playing a role in showing their strong, creative, independent and professional excellence in their respective fields. The purpose of this study is to determine the effectiveness of the application of problem-based learning in the course of improving critical thinking skills in social studies subjects. This study uses a type of experimental learning with a quantitative approach. The method used in this study is pre-experiment with a learning design, namely one-shot case study. The sample used in this study was determined by using the purposive sampling method, namely 17 students in grade VIII. In-depth data collection in this study uses test instruments, namely pre-test and post-test which are then analyzed using the N-gain score test. The results of the analysis show that the N-gain score (%) = 60.88 so that it can be concluded that the application of problem-based learning is quite effective in improving critical thinking skills in social studies subjects, placing participants in an active position as problem solvers, encouraging them to analyze, evaluate, and synthesize information. This condition provides an opportunity for students to develop critical thinking skills which are much needed in this era of globalization. Keywords: problem-based learning, critical thinking, learning effectiveness